Combining synchrotron vacuum-ultraviolet photoionization mass spectrometry and gas chromatography–mass spectrometry for isomer-specific mechanistic analysis with application to the benzyl self-reaction - Guangxian Xu; Hong Wang; Jinyang Zhang; Jiao Gao; Jiwen Guan; Qiang Xu; Donald G. Truhlar; Zhandong Wang (Nature Communications)
Abstract Elucidating the formation mechanism of polycyclic aromatic hydrocarbons (PAHs) is crucial to understand processes in the contexts of combustion, environmental science, astrochemistry, and nanomaterials synthesis. An excited electronic-state pathway has been proposed to account for the formation of 14π aromatic anthracene in the benzyl (b-C7H7) self-reaction. Here, to improve our understanding of anthracene formation, we investigate C7H7 bimolecular reactions in a tubular SiC microreactor through an isomer-resolved method that combines in situ synchrotron-radiation VUV photoionization mass spectrometry and ex-situ gas chromatography–mass spectrometry. We observe the formation of o-tolyl (o-C7H7) radical isomer, and identify several C14H10 products (diphenylacetylene, phenanthrene and anthracene) and key C14H14 and C14H12 intermediates. These isomer-specific results support the occurrence of reactions on the electronic ground-state potential energy surface, with no evidence for key intermediates of the proposed excited-state pathway as the key pathway. Furthermore, theoretical calculations unveil new facile reaction pathways that may contribute to the enhanced production of anthracene, and these mechanistic findings are further substantiated by pyrolysis experiments. The results add insight into the molecular formation of PAHs in C7H7 bimolecular reaction, and contribute to establishing accurate models to predict PAH chemistry in diverse laboratory, environmental, and extraterrestrial contexts.